Hadith #347 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Hasan al-Basri الحسن البصري; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Khayra Umm al-Hasan al-'Abbassri خيرة أم الحسن البصري; Muhammad bin Ishaq al-Saghani محمد بن إسحاق الصغاني; Qatada قتادة; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية (Sunan al-Nasa'i)
It was narrated from ‘Aishah that the Messenger of Allah (ﷺ) used to perform Ghusl with a Mudd and Ghusl with approximately a Sa’.
Grade:

Hadith #2382 - Sunan al-Nasa'i - Abdullah bin Ma'bd عبد الله بن معبد الزماني; Abu Qatada ibn Rab'i; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ghaylan bin Jarir غيلان بن جرير المعولي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Muhammad bin Sulaym محمد بن سليم أبو هلال الراسبي; Umar ibn al-Khattab (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The one who fasts every day of his life has neither fasted, nor broken the fast.”‘ ‘Ata said: “someone who heard him told me that Ibn ‘Umar (said) that the Prophet said: ‘Whoever fasts every day of his life, then he has not fasted.”
Grade:

Hadith #2989 - Sunan al-Nasa'i - al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ata' bin Abi Rabah عطاء بن أبي رباح; Hammad bin Salama حماد بن سلمة; Mu'awiya ibn Abu Sufyan; Muhammad bin Mansur bin Da'ud محمد بن منصور بن داود الطوسي; Qays ibn Sa'd ibn 'Ubadah (Sunan al-Nasa'i)
the Messenger of Allah came down from As-Safa until he reached level round in the valley, then he hastened (Ramel) until (the ground) rouse, then he walked.
Grade:

Hadith #3843 - Sunan al-Nasa'i - al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ibrahim bin Y'aqub bin Ishaq إبراهيم بن يعقوب بن إسحاق; Imran bin Husain; Muhammad bin al-Zubair al-Hanzali محمد بن الزبير الحنظلي; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“There is no vow to commit an act of disobedience and its expiation is the expiation for an oath.”
Grade:

Hadith #5272 - Sunan al-Nasa'i - al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ali ibn Abi Talib; Ibrahim bin Y'aqub bin Ishaq إبراهيم بن يعقوب بن إسحاق; Khalid bin Ma'dan خالد بن معدان; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
The Messenger of Allah said: “Any woman who has been perfumed with incense should not attend ‘Isha’ the later with us.”
Grade:

Hadith #937 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; ibn Umar; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Mujahid bin Jabir مجاهد بن جبر; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية (Jami' al-Tirmidhi)
Ibn Umar was asked: In which month did the Messenger of Allah perform Umrah? He said: ‘During Rajab.’ So Aishah said: ‘The Messenger of Allah did not perform Umrah except that he was with him – meaning Ibn Umar – and he did not ever perform Umrah in the month of Rajab.'”
Grade:

Hadith #1229 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ibn Sirin محمد بن سيرين الأنصاري; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية (Jami' al-Tirmidhi)
] This Hadith is Hasan Sahih, and this is acted upon according to the people of knowledge. It is the view of Ash-Shafi’i and our companions.
Grade:

Hadith #2706 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abu Sa'id al-Khudri; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب (Jami' al-Tirmidhi)
that the Messenger of Allah (ﷺ) said: “Whoever lifts the curtain so that his sight enters the house before he was given permission, and he seeks the nakedness of its inhabitants, then he has done something punishable which was not lawful for him to do. If it were that when he gazed into it, he was facing a man who lanced his eyes, there would be nothing wrong with him doing so. But if a man passes by a door that has no cover over it, and it is not closed and he looks, then there is no sin on
Grade:

Hadith #2970 - Jami' al-Tirmidhi - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Manay' أحمد بن منيع; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية (Jami' al-Tirmidhi)
“When ‘Until the white (light) thread of dawn appears distinct to you from the black thread (of night)’ was revealed, the Prophet (ﷺ) said to me: ‘That only refers to the whiteness of the day from the blackness of the night.'”
Grade:

Hadith #3112 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Asim al-Ahwal عاصم الأحول; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Ubayy ibn Ka'b; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Jami' al-Tirmidhi)
“A man came to the Prophet (ﷺ) and said: ‘I fondled a woman who lives on the edge of Al-Madinah, and I did with her what is less than intercourse, and here I am, so judge in my case as you will.’ So ‘Umar said to him: ‘Allah covered you, so you should have covered yourself.’ The Messenger of Allah (ﷺ) did not give him any reply. The man left but the Messenger of Allah (ﷺ) sent a man after him to call him. He recited to him: ‘And perform Salat, at the two ends of the day and i
Grade:

Hadith #3163 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; ibn Abbas; Ja'far bin Abi al-Mughira جعفر بن أبي المغيرة الخزاعي; Sa'id bin Jubayr سعيد بن جبير الأسدي (Jami' al-Tirmidhi)
“While the Messenger of Allah (ﷺ) was returning from Khaibar he traveled during the night until he became sleepy and he sat down to rest. Then he said: ‘O Bilal! Stand guard for us for the night.'” He said: ‘So Bilal performed Salat, then he leaned against his mount facing the direction of (dawn awaiting) Fajr. His eyes overcame him until he slept, and not one of them awoke. The first of them to awaken was the Prophet (ﷺ) who said: ‘O Bilal!’ Bilal said: ‘May my father be ranso
Grade:

Hadith #3175 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Aisha bint Abi Bakr; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Hammad bin Salama حماد بن سلمة; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء (Jami' al-Tirmidhi)
that ‘Aishah the wife of the Prophet (ﷺ) said: “I asked about the Messenger of Allah (ﷺ) about this Ayah: And those who give that which they give with their hearts full of fear… (23:60)” ‘Aishah said: “Are they those who drink Khamr and steal?” He said: “No, O daughter of As-Siddiq. They are those who fast, perform Salat, give charity while they fear that their Lord will not accept it from them: It is these who hasten to do good deeds, and they are the foremost of them (23:61
Grade:

Hadith #3351 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abu Hurairah; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Hammad bin Salama حماد بن سلمة; Sulaiman bin Harb سليمان بن حرب (Jami' al-Tirmidhi)
“I said to Ubayy bin Ka’b: ‘Your brother Abdullah bin Mas’ud says: “Whoever stands (in voluntary prayer) the whole year, then he will have reached the Night of Al-Qadr.’” So he said: ‘May Allah forgive Abu Abdur-Rahman. He knows that is during the last ten (nights) of Ramadan, and that it is the night of the twenty-seventh. But he wanted the people to not rely upon that.’ Then he uttered an oath, that without exception it is on the night of the twenty-seventh.” He said: “I
Grade:

Hadith #3376 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abu Sa'id al-Khudri; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب (Jami' al-Tirmidhi)
the Prophet said: “Should I not inform you of the best of your deed, and the purest of them with your Master, and the highest of them in your ranks, and what is better for you than spending gold and silver, and better for you than meeting your enemy and striking their necks, and they strike your necks?” They said: “Of course.” He said, “The remembrance of Allah said: “There is nothing that brings more salvation from the punishment of Allah than the remembrance of Allah.”
Grade:

Hadith #3560 - Jami' al-Tirmidhi - Abd bin Hameed bin Nasr عبد بن حميد بن نصر; Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abu Sa'id al-Khudri; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب (Jami' al-Tirmidhi)
That the Prophet (ﷺ) sent an expedition in the direction of Najd. They gained many spoils of war and returned quickly. A man among those who did not go out said: “We have not seen an expedition quicker in return or greater in spoils than this expedition.” So the Messenger of Allah (ﷺ) said: “Should I not direct you to a group greater in spoils and quicker in return? A group who attended Salat As-Subh, then sat remembering Allah until the sun rose, for these are quicker in return and gr
Grade:

Hadith #42 - Sunan Ibn Majah - al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Muhammad bin 'Abdullah bin Qahzad محمد بن عبد الله بن قهزاد (Sunan Ibn Majah)
“The Messenger of Allah saw me urinating while standing, and he said: ‘O ‘Umar, do not urinate standing up.’ So I never urinated whilst standing after that.”
Grade:

Hadith #752 - Sunan Ibn Majah - Abdur Rahman Ibn 'Awf; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“The Prophet (ﷺ) sent me on an errand, then I caught up with him while he was performing prayer, and I greeted him. He gestured to me, then when he finished, he called me and said: ‘You greeted me before, but I was performing prayer.’”
Grade:

Hadith #2359 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Ali bin Zayd bin 'Abdullah bin Zuhayr علي بن زيد بن عبد الله بن زهير; Hammad bin Salama حماد بن سلمة (Sunan Ibn Majah)
“Whoever suffers from killing or wounding, has the choice of three things, and if he wants the fourth then restrain him. He may kill (the killer), or forgive him, or take the blood money. Whoever accepts any of these (options), then kills (the killer) after that will have the fire of hell to abide therein forever.”
Grade:

Hadith #3376 - Sunan Ibn Majah - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Amr bin Dinar al-Basri عمرو بن دينار البصري الأعور قهرمان; ibn Umar; Sa'id bin Zayd; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar ibn al-Khattab (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade wearing gold rings.”
Grade:

Hadith #3410 - Sunan Ibn Majah - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Amr bin Dinar al-Basri عمرو بن دينار البصري الأعور قهرمان; ibn Umar; Sa'id bin Zayd; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar ibn al-Khattab (Sunan Ibn Majah)
“We said to the Messenger of Allah(ﷺ): ‘ You send us and we stay with people who do not show us any hospitality. WHat do you think of that?’ The MEssenger of Allah (ﷺ) said: ‘If you stay with people and they give you what a guest deserves, then accept it. If they do not do that , then take from them what they should have offered, which a guest is entitled to.'”
Grade:

Hadith #3689 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Qatada قتادة; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية (Sunan Ibn Majah)
“There will be tribulation in which a man will be a believer in the morning and a disbeliever by evening, except the one to whom Allah grants knowledge.”
Grade:

Hadith #3865 - Sunan Ibn Majah - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Salama حماد بن سلمة; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Ibn Majah)
“Woe to the most wealthy except those who do such and such with the money, and such and such” – four things, (pointing) to his right, to his left, in front of him and behind him.
Grade:

Hadith #3918 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; al-Musayb bin Rafa'i al-Asadi المسيب بن رافع الأسدي الكاهلي أبو العلاء; Asim bin Abu al-Najud; Hammad bin Salama حماد بن سلمة; Kharsha bin al-Hurr al-Fazari (Sunan Ibn Majah)
“Every religion has its distinct characteristic, and the distinct characteristic of Islam is modesty.’”
Grade: